Limited support for trunk and hip deficits as risk factors for athletic knee injuries: A systematic review with meta-analysis and best-evidence synthesis - Chia, L.; de Oliveira Silva, D.; McKay, M. J.; Sullivan, J.; Micolis de Azevedo, F.; Pappas, E. (Journal of Orthopaedic & Sports Physical Therapy, 2020)
Objective: To determine if neuromuscular deficits in trunk and hip-related function are risk factors for athletic knee injuries. Design: Aetiology systematic review with meta-analysis. Literature Search: Six online databases (MEDLINE, Web of Science, EMBASE, CINAHL, Scopus and SPORTDiscus) searched until April 2019. Study Selection Criteria: Studies assessing trunk and hip neuromuscular function as risk factors for knee injuries in healthy athletic populations were included. Data Synthesis: Outcomes synthesized quantitatively using meta-analysis of odds ratios, and qualitatively using best-evidence synthesis. Results: Twenty-one studies met the inclusion criteria. There was very low-credibility evidence that greater hip external rotation strength was protective of knee injuries (OR 0.78, 95% CI: 0.70, 0.87, p < 0.05). There was limited evidence that deficits in trunk proprioception and neuromuscular control, and the combination of excessive knee valgus and ipsilateral trunk angle when landing unilaterally from a jump may be risk factors for knee injuries. Conclusion: Most variables of trunk and hip function identified in this review were not risk factors for future athletic knee injuries. Further research is required to confirm if hip external rotation strength, trunk proprioception and neuromuscular control, and the combination of knee valgus angle and ipsilateral trunk control are risk factors for future knee injuries